Basic Scholarship in Biosafety Is Critically Needed To Reduce Risk of Laboratory Accidents - Ryan Ritterson (American Society for Microbiology, 2017)
ABSTRACT Our firm conducted a risk/benefit assessment of “gain-of-function” research, as part of the deliberative process following a U.S. moratorium on the research (U.S. Department of Health and Human Services, U.S. Government Gain-of-Function Deliberative Process and Research Funding Pause on Selected Gain-of-Function Research Involving Influenza, MERS, and SARS Viruses, 2014). Due to significant missing but theoretically acquirable data, our biosafety assessment faced limitations, and we were forced to provide a relative, instead of absolute, measure of risk (Gryphon Scientific, LLC, Risk and Benefit Analysis of Gain of Function Research, 2016). Here, we argue that many of these types of missing data represent large and stunning gaps in our knowledge of biosafety and argue that these missing data, once acquired via primary research efforts, would improve biosafety risk assessments and could be incorporated into biosafety practices to reduce risk of accidents. Governments invest billions in biological research; at least a small fraction of this support is warranted to prevent biological accidents.